2010
DOI: 10.1017/s1751731110001266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastrointestinal transit times between chickens from D+ and D− genetic lines selected for divergent digestion efficiency

Abstract: D 1 (high digestion efficiency) and D 2 (low digestion efficiency) genetic chicken lines selected for divergent digestion efficiency were compared in this experiment. Gizzard functions were tested in terms of digesta mean retention time and reactions to high dilution of a corn diet with 15% coarse sunflower hulls. The corn standard (S) and high fibre (F) experimental diets were given from 9 days of age to chickens from both lines. Besides the measurements of growth efficiencies (9 to 20 days), digestibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 40 publications
(68 reference statements)
9
62
0
5
Order By: Relevance
“…Structural feed components have been reported to be retained in the gizzard for a longer time (Rougière & Carré 2010;Svihus 2011;Meremikwu et al 2013). The high fibre content of the test diet which must have resulted in increased digesta retention time in the gastro-intestinal tract may be a reason for the lower feed intake observed in the present experiment.…”
Section: Resultsmentioning
confidence: 57%
“…Structural feed components have been reported to be retained in the gizzard for a longer time (Rougière & Carré 2010;Svihus 2011;Meremikwu et al 2013). The high fibre content of the test diet which must have resulted in increased digesta retention time in the gastro-intestinal tract may be a reason for the lower feed intake observed in the present experiment.…”
Section: Resultsmentioning
confidence: 57%
“…This suggests that the birds which have been specifically selected for high digestive efficiency are genetically predisposed to growing a large gizzard. The gizzard size may also play a vital role in improving digestive efficiencies by increasing the mean digesta retention time, described by some as the greatest influencing factor in the improvement of digestive efficiency (Pym 1985;Maisonnier et al 2001;Pishnamazi et al 2005;González-Alvarado et al 2008;Rougière and Carré 2010). Therefore, should digestive efficiency have increased, the gizzard might be expected to be larger in modern broilers relative to body mass.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…Contrasting correlations in relative organ sizes have been discovered between lines selected for commercial objectives and high digestive efficiency (Carré et al 2005;Péron et al 2006;Rougière and Carré 2010;de Verdal et al 2010). For instance, Mussini (2012) showed that the gizzard is significantly smaller, and the pancreas similar, in modern commercial breeds when compared to old-type breeds fed on the same diet.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of fibrous ingredients in poultry diets reduces feed intake (FI) (Kondra et al, 1974;Sklan et al, 2003) and nutrient digestibility (Rougière and Carré, 2010) and might affect the incidence of enteric disorders in poultry (Montagne et al, 2003;Shakouri et al, 2006;Mateos et al, 2012). Recent research conducted with young broilers, however, have shown that the inclusion of moderate amounts of insoluble fiber sources, such as oat hulls (OH) and sunflower hulls (SFH), in the diet stimulates the development and physiology of the gastrointestinal tract (GIT) Svihus, 2011;Sacranie et al, 2012) and might improve broiler performance González-Alvarado et al, 2010).…”
Section: Introductionmentioning
confidence: 99%